Digitalization and Social Protection : Macro and Micro Lessons for Vietnam - Hosny, Amr.; Sollaci, Alexandre (Washington, D.C. : International Monetary Fund, 2022)
The COVID-19 shock has underscored the importance of digital tools for enhancing the effectiveness and efficiency of social protection systems. Cross-country evidence suggests that digital IDs linked with bank and/or mobile money accounts can improve the delivery of social protection programs and better reach eligible beneficiaries. Using data from the Vietnam Household Living Standard Survey, we present micro simulations on the welfare gains of digital social protection during the pandemic. While digitalization offers opportunities, potential risks would need to be carefully managed. Vietnam is advancing on individual pieces of the digitalization puzzle, including full digital IDs and mobile money, and the next step is to put these pieces together.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policies and Behavior of Economic Agents; Plant Closings; Severance Pay; Simulation Methods; Unemployment Insurance